Neoagarohexaose-mediated activation of dendritic cells via Toll-like receptor 4 leads to stimulation of natural killer cells and enhancement of antitumor immunity - Lee, Moon Hee; Jang, Jong-Hwa; Yoon, Gun Young; Lee, Seung Jun; Lee, Min-Goo; Kang, Tae Heung; Han, Hee Dong; Kim, Hyuk Soon; Choi, Wahn Soo; Park, Won Sun; Park, Yeong-Min; Jung, In Duk (BMB reports, 2017)
β-Agarase cleaves the β-1,4 linkages of agar to produce neoagarooligosaccharides (NAO), which are associated with various physiological functions. However, the immunological functions of NAO are still unclear. In this study, we demonstrated that β-agarase DagA-produced neoagarohexaose (DP6), an NAO product, promoted the maturation of dendritic cells (DCs) by Toll-like receptor 4 (TLR4). DP6 directly and indirectly enhanced the activation of natural killer (NK) cells in a TLR4-dependent manner in vitro and in vivo. Finally, the antitumor activity of DP6 against B16F1 melanoma cells was inhibited in NK cell-depletion systems by using NK-cell depleting antibodies in vivo. Collectively, the results indicated that DP6 augments antitumor immunity against B16F1 melanoma cells via the activation of DC-mediated NK cells in a TLR4-dependent manner. Thus, DP6 is a potential candidate adjuvant that acts as an immune cell modulator for the treatment of melanoma. [BMB Reports 2017; 50(5): 263-268].